2019
DOI: 10.15244/pjoes/99242
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Heavy Metals in Karst Region Soil and the Enrichment Characteristics of Rice-Rape Rotation

Abstract: Cultivated land is the most precious non-renewable resource, the foundation of grain production and the material basis of the survival and development of human beings [1]. China's cultivated land per capita is lower than world average due to the limited area and the insufficient reserve resources [2]. Since China implemented strict arable land polity in the 1990s, targeted protective measures have been gradually performed, but there are no obvious effects. According to the statistics from the Ministry of Land … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The author of this article was more inclined to the findings of Zhang et al, possibly because of the geographical location of the trial sites. This study and that of Zhang et al et al were both located in the suburbs, but the study of other researchers [20] was located along the highway. Although they were all affected by human activities to a large extent, the different ways and methods of influence might lead to different findings.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The author of this article was more inclined to the findings of Zhang et al, possibly because of the geographical location of the trial sites. This study and that of Zhang et al et al were both located in the suburbs, but the study of other researchers [20] was located along the highway. Although they were all affected by human activities to a large extent, the different ways and methods of influence might lead to different findings.…”
Section: Discussionmentioning
confidence: 74%
“…However, among the heavy metal Zn in bottom soil, the exchangeable fraction was significantly positively correlated with the Fe/Mn oxide, organic matter-bound, and residual fractions. This might be due to the fact that Eh in the bottom soil is much higher than that in the top soil, making the residual fraction of heavy metal Zn in the bottom soil increase substantially [22]. From the soil surface to 0-40 cm below vertically, it was found that the residual fraction of heavy metal Zn in soil was significantly negatively correlated with the carbonatebound, Fe/Mn oxide, and organic matter-bound fractions.…”
Section: Discussionmentioning
confidence: 98%
“…The results indicated that the health risk of heavy metal through vegetable intake on children was higher than that of adults. Much research [54][55][56] has indicated that children were typically more susceptible to a given dose of toxins than adults in the case of heavy metal exposure through diet, which were likely to inadvertently ingest significant quantities of heavy metals in agricultural products. Table 8.…”
Section: Health Risk Assessment Of Agricultural Productsmentioning
confidence: 99%
“…The first national pollutant survey reflected that the concentration of arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), mercury (Hg), nickel (Ni), lead (Pb) and zinc (Zn) in the surface soils of Guangxi were 2.0, 4.5, 1.6, 1.1, 2.6, 1.3, 1.4 and 1.4 times than that of the surface soils of China, respectively. However, part of croplands with high heavy metal geological settings were used to culture crops owing to the finite arable land per capita in China, especially the karst area in Southwest China [12].…”
Section: Introductionmentioning
confidence: 99%
“…Parent material determines the heavy metal content in soil [13]. At present, there is a lot of research on soil heavy metal pollution in karst areas [10,[12][13][14]. In karst areas, carbonate rocks intercalated with clastic rocks or interbedded between the two are common.…”
Section: Introductionmentioning
confidence: 99%